Caracterização da variabilidade gerada por hibridações artificiais e mutações em caracteres de importância agronômica em aveia preta. - Silveira, Gustavo da (2009)
Black oat (Avena strigosa Schreb.) is used as a forage or cover crop, green fertilizer, weed control (through competition or allelopatic effects) and soil pathogen reduction, playing an important role in crop rotation systems. Even with all these features, the high heterogeneity found in black oat fields indicates that very little progress has been made in breeding programs. Not much is known about yield potential, chemical composition of the forage and seed dormancy levels. Thus, the development of new genotypes with high forage yield performance as well as good seed quality and low dormancy will provide alternatives for the common black (preta comum) cultivar, currently predominating in the Southern Region of Brazil. Genetic variability widening can be achieved by artificial crosses and induced mutations, followed by selection. Therefore, black oat populations originating from artificial crosses and induced mutations (gamma rays) were compared in order to assess their efficiency in increasing the genetic variability. Agronomically important characters, i.e., associated to adaptation and farmer needs were measured. The results indicate that both techniques were efficient in increasing the genetic variability of forage characters, grain yield and seed dormancy levels. A high association was observed between plant stand and dry matter yield in early developmental stages. At later stages, the number of tillers was highly associated with biomass yield. In general, for both artificial hybridizations and gamma rays, differences in grain yield and seed dormancy levels were observed. Doses as well as parental combinations influenced the magnitude of the variability observed. The comparison of such techniques may help to accelerate the genetics gains in the black oat crop.